The Effect of Human Resource Competence on Employee Performance through Organizational Citizenship Behavior (OCB) as a Mediating Variable in the National Unity and Political Agency of Western Seram Regency - Souhoka, Semuel (West Science Business and Management, 2025)
At the Agency for National Unity and Politics of West Seram Regency, this study intends to examine the relationship between employee performance and human resource competency, using organizational citizenship behavior (OCB) as a mediating variable.  37 employees participated in the quantitative study, which used Partial Least Squares (PLS) to analyze the data.  The results show that: (1) human resource competency considerably affects employee performance; and (2) human resource competency greatly affects OCB.; (3) OCB is significantly impacted by employee performance; and (4) OCB mediates the relationship between human resource competency and employee performance.  The R-squared values show that OCB can be described by human resource competence by 56.4%, while employee performance can be explained by both OCB and HR competency by 38.8%. These findings are consistent with the competency theory of Spencer & Spencer (1993) and Organ’s OCB theory (1988), and reinforce previous studies emphasizing the importance of competence and extra-role behavior in enhancing employee performance. The study recommends continuous development of human resource competence and the creation of a supportive work climate that encourages OCB as strategic efforts to improve employee performance in the public sector.